Location and Extent of Deep Vein Thrombosis in Patients with and without FV:R 506Q Mutation - Björgell, Ola; Nilsson, Paul E.; Nilsson, Jan-Åke; Svensson, Peter J. (Thrombosis and Haemostasis, 2000)
Resistance to activated protein C due to FV:R 506Q mutation is the most common known genetic risk factor for deep leg vein thrombosis (DVT). The aim of this prospective study was to describe and compare the location and extent of DVT, reflected by a scoring system, in a group of patients with and without FV:R 506Q mutation. Of 247 consecutively included patients undergoing phlebography 105 had a DVT, 36 (35%) in the FV:R 506Q mutation group and 69 (65%) in the non-FV:R 506Q mutation group. Compared to the non-FV:R 506Q mutation group there was a significant increase in the incidence of DVT in the FV:R 506Q mutation group (p = 0.041, OR = 1.79 [1.02–3.15]), a significantly lower mean DVT score of the iliofemoral vein segments (p = 0.0081) and a significantly lower incidence of DVT in the iliofemoral vein segments (p = 0.007, OR = 10.6 [1.3–83.3]), 1/36 (2.8%) compared to 16/69 (23.2%). As controls 288 blood donors were included, with and without FV:R 506Q mutation and with no history of DVT in order to evaluate risk factors of DVT. The odds ratio of an iliofemoral DVT was 0.5 ([0.06–3.90), p = 0.50]) when FV:R 506Q mutation was present, compared to the control group, and at locations below the iliofemoral segments 5.28 ([3.01–9.28], p = less than 0.0001). Our findings provide the basis of a detailed phlebographic description and for the first time, to our best knowledge, shows a specific phlebographic pattern that may be linked to an inherited hypercoagulable state.
Keywords: Score; phlebography; deep leg vein thrombosis; FV:R 506Q mutation; pulmonary embolism